2017
DOI: 10.1039/c7sm01043e
|View full text |Cite
|
Sign up to set email alerts
|

From a silane monomer to anisotropic buckled silica nanospheres: a polymer-mediated, solvent-free and one-pot synthesis

Abstract: The morphology of particles, along with other particle attributes, has been shown to affect the biological fate of particles administered into the body. Particles with collapsed surfaces or shells (dimpled, buckled or crumpled) can have different appearances, under the microscope, that resemble many things encountered in our daily life, such as apples/cherries, doughnuts, and bowls. Recent studies have demonstrated that they are not just particles with interesting geometries, but they can also be used as funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…6 Lo et al reported a series of anisotropic buckled silica nanoparticles, including apple-like, doughnut-like, and bowl-like nanoparticles, with mercaptopropyl trimethoxysilane as the only silane source. 20 Hao et al fabricated biomimic walnut kernellike and erythrocyte-like mesoporous silica nanoparticles with two surfactants. They further identified that these silica nanoparticles performed superiorly in cellular imaging and drug delivery.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Lo et al reported a series of anisotropic buckled silica nanoparticles, including apple-like, doughnut-like, and bowl-like nanoparticles, with mercaptopropyl trimethoxysilane as the only silane source. 20 Hao et al fabricated biomimic walnut kernellike and erythrocyte-like mesoporous silica nanoparticles with two surfactants. They further identified that these silica nanoparticles performed superiorly in cellular imaging and drug delivery.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zhou et al fabricated golf ball-like organic–inorganic silica microspheres with a wrinkled surface . Lo et al reported a series of anisotropic buckled silica nanoparticles, including apple-like, doughnut-like, and bowl-like nanoparticles, with mercaptopropyl trimethoxysilane as the only silane source . Hao et al fabricated biomimic walnut kernel-like and erythrocyte-like mesoporous silica nanoparticles with two surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Lo et al obtained buckled bowl-like organosilica nanoparticles (50−60 nm in diameter) using 3-mercaptopropyl trimethoxysilane as a silane source in an aqueous solution containing poly(vinyl alcohol). 27 The buckled nanoparticles formed as a result of drying. Ma et al reported the synthesis of sub-10 nm silica nanoparticles bearing half-pores by using micelles of hexadecyltrimethylammonium hydroxide as templates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Only a few reports demonstrated the preparation of single-hole nanoparticles smaller than 100 nm in diameter. Lo et al obtained buckled bowl-like organosilica nanoparticles (50–60 nm in diameter) using 3-mercaptopropyl trimethoxysilane as a silane source in an aqueous solution containing poly­(vinyl alcohol) . The buckled nanoparticles formed as a result of drying.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] Previously, there have been several attempts to prepare organosilica particles in a solvent-free system, based mainly on acidic or basic routes. [32][33][34][35][36][37] Most recently, we have demonstrated a general "salt route" for efficiently synthesizing organosilica nanospheres in purely aqueous reaction systems containing common salts and common surfactants or polymers. 38 We demonstrated that under the mild reaction conditions (neutral pH, room temperature, no stirring), stable colloidal solutions containing organosilica nanoparticles (about 100 nm) could be produced within 24 h. 38 Fluoride ion (F À ) has been used as a catalyst to mediate the hydrolysis and condensation of silica precursors and form mesoporous or microporous solid materials.…”
Section: Introductionmentioning
confidence: 99%